Respuesta :

9514 1404 393

Answer:

  f(x) +g(x) = 4x^2 +3

  f(x) -g(x) = 4x^2 -6x +1

  f(x)·g(x) = 12x^3 -5x^2 +3x +2

Step-by-step explanation:

Substitute for f(x) and g(x) and simplify.

(a)  f(x) +g(x) = (4x^2 -3x +2) +(3x +1)

  f(x) +g(x) = 4x^2 +3

__

(b)  f(x) -g(x) = (4x^2 -3x +2) -(3x +1)

  f(x) -g(x) = 4x^2 -6x +1

__

(c)  f(x)·g(x) = (4x^2 -3x +2)(3x +1)

  = (4x^2 -3x +2)(3x) +(4x^2 -3x +2)(1) . . . use the distributive property

  = 12x^3 -9x^2 +6x +4x^2 -3x +2

  f(x)·g(x) = 12x^3 -5x^2 +3x +2

Answer:

a.) f( x ) + g( x ) = 4 x² + 3

b.) f( x ) - g ( x ) = 4x² -6x + 3

c.)f ( x ) . g ( x ) = 12x³ - 5x² + 3x + 2

Step-by-step explanation:

Given :- f ( x) = 4x² - 3x + 2 and g(x)= 3x +1

Substitute the values of f(x) and g(x) and simplify all .

a.) f( x ) + g( x )

( 4x² - 3x + 2 ) + ( 3x + 1 )

4 x² - 3x + 2 + 3 x + 1

collect like terms

4x² - 3 x + 3 x + 2 + 1

4 x² + 3

b.) f ( x ) - g ( x )

( 4x² - 3x + 2 ) - ( 3x + 1 )

4x² - 3x + 2 - 3x - 1

collect like terms

4x² - 3 x - 3x + 2 - 1

4x² -6x + 1

c.) f ( x ) . g ( x )

( 4x² - 3x + 2 ) × ( 3x + 1 )

Use the Distributive property

3 x(4x² - 3x + 2 ) × 1 ( 4x² - 3x + 2 )

Remove the parantheses multiply

12x³ - 9x² + 6x + 4x² - 3x + 2

Collect like terms

12 x³- 9x ² + 4x² + 6x - 3x + 2

12x³ - 5x² + 3x + 2

ACCESS MORE